Study the kinetics involved in solid state reduction of mill scale with lean grade coal and optimization of process parameters involved in reduction through rotary kiln furnace. (2021) - Shekhawat, Deepika; Kukshal, Vikas; Banerjee, M.K.; Patnaik, Amar
Abstract: Present investigation envisages kinetics involved in solid state reduction of mill scale surrounded by lean grade coal powder in static and dynamic processes. Research aims to evaluate the reduction potential of economically available lean grade coal from Rajasthan in the reduction of mill scale. Experiments were carried out by mixing equal proportion of mill scale and coal and charging into the rotary kiln furnace. The variables studied are time and temperature. The reduction was done at temperatures ranging from 950 °C to 1050 °C. The degree of reduction of mill scale was calculated at 60 to 240 min. The experiments were statistically designed to assess each variable quantitatively and compared. The results indicated an increase in the degree of reduction with time and temperature. With the increment in temperature up to 1000 °C and holding time 240 min, 77.71% of metallization is achieved. The results showed a definite relation between reduction with time and temperature. Using the technique of empirical relation of transformation, the kinetics involved in solid state reduction of iron is studied for the processes. It is empirically calculated that the kinetics of reduction for the process of reduction in rotary kiln using the experimented setup. The Taguchi method, and analysis of variance (ANOVA) for the selected parameters to investigate the major effects and to assess the optimal process parameters show that, temperature is the most significant parameter amongst all whereas the mill scale size is the least affecting parameter. Based upon the analysis the optimized parameters obtained were temperature (at 1000 °C), mill scale to coal ratio (minimum 1:3), time (minimum 180 min), and mill scale size (minimum 425 to 600 µm). The microstructural characterization (XRF, XRD and FE-SEM. FE-SEM) conforms the formation of porous mass due to the solid state reaction between mill scale and coal.